Microclimate Control in The Affandi Museum Gallery Yogyakarta - Bambang Pramono; Danang Febriyantoko (TUMATA: Journal of Arts and Cultural Management, 2025)
Affandi Koesoema is one of the most internationally renowned Indonesian painters because of his typical expressionist and romantic style. His legendary works are still stored in his private museum, designed  with Affandi's design and construction. The building was not originally designed as a museum by Affandi, so in practice, many adjustments were made to the conditional arrangements. Indonesia's tropical climate with relatively high humidity and temperatures requires museum managers to adapt to fluctuating air temperatures. Efforts to preserve the work of Affandi paintings have been made to maintain the sustainability of Indonesian painting art. One of the considerations that should also be given attention is regarding technical aspects, including the engineering of the museum environment, that can be done to protect the invaluable art and cultural assets. Temperature control and room humidity are very important in museums and art galleries; if the room is too hot or cold, too humid or dry, it will affect the quality of the painting. This research aims to find out how environmental engineering is done at the museum to preserve the masterpiece of Affandi's painting art. The aspects of thermal comfort and humidity were one of the considerations in  analyzing this study, given the tropical climate conditions that also affected art conservation activities.